THE INFLUENCE OF ACCOUNTABILITY, TRANSPARENCY, AND PROFESSIONALISM OF INSTITUTIONS ON THE LEVEL OF MUZAKKI'S TRUST IN PAYING ZAKAT AT LAZISNU DIY - Adamy, M. Fikrul Humam; Faozi, Mohammad; Gustanto, Edo Segara; Kamilulloh, Farhan (Jurnal Asy-Syukriyyah, 2024)
The purpose of this research is to determine the influence of accountability on the level of trust of Muzakki in Paying Zakat at PWNU Care LAZISNU DIY (Daerah Istimewa Yogyakarta, the influence of transparency on the level of trust of muzakki in paying zakat at PWNU Care LAZISNU DIY, the influence of professionalism on the level of trust of muzakki in paying zakat at PWNU Care LAZISNU DIY, and the influence of accountability, transparency, and professionalism on the level of trust of muzakki in paying zakat at PWNU Care LAZISNU D.I.Y. This research falls under the category of quantitative research, where the study is associated with numbers, tables, and graphs, utilizing the SPSS 26 tool to determine the results of validity tests, reliability tests, multiple linear regression, t-tests, F-tests, and coefficient of determination (R2). The sample used consisted of 83 Muzakki with a random sampling technique, and a questionnaire was employed as the data collection method. The results of this research indicate that accountability, transparency, professionalism, and accountability have a significant negative effect on the level of trust of Muzakki. Additionally, the variables of Accountability, Transparency, and Professionalism of the institution collectively and significantly influence the Level of Trust of Muzakki.